2019
DOI: 10.1007/s12105-019-01032-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Follicular Thyroid Neoplasm with Papillary-Like Nuclear Features is Rare: A Population Based Study of Incidence

Abstract: The renaming of encapsulated follicular variant of papillary thyroid carcinoma (EFVPTC) to noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was proposed by a group of experts in 2016 to prevent overtreatment of indolent, low-risk thyroid cancers. The aim of this study was to estimate the incidence and outcome for patients meeting the NIFTP criteria in a well-defined geographic region. Our cohort consisted of 134 patients with papillary thyroid carcinoma from the Region of So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Based on available evidence from several studies of molecular profiling, a relevant portion of NIFTPs carry RAS mutations. In fact, the review of 18 studies [52,53,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] showed a wide range of prevalence for RAS mutations, from 20 to 100%. This could be related to the heterogeneity of tumor series coming from different geographic areas and different source (cytology samples or tumor specimens), and detection method (direct sequencing, PCR-based approaches, or next-generation sequencing [NGS] technology).…”
Section: Prevalence Of Ras Mutations In Thyroid Nodular Diseasementioning
confidence: 99%
“…Based on available evidence from several studies of molecular profiling, a relevant portion of NIFTPs carry RAS mutations. In fact, the review of 18 studies [52,53,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] showed a wide range of prevalence for RAS mutations, from 20 to 100%. This could be related to the heterogeneity of tumor series coming from different geographic areas and different source (cytology samples or tumor specimens), and detection method (direct sequencing, PCR-based approaches, or next-generation sequencing [NGS] technology).…”
Section: Prevalence Of Ras Mutations In Thyroid Nodular Diseasementioning
confidence: 99%
“…15,19,22,23 While a nuclear scoring scheme could introduce a more structured approach to classification, concerns about intra-and interobserver variability and inconsistent reports remain. 14,24,25 Zajkowska and Strickland addressed the problem with the NIFTP entity. 26,27 In particular, Strickland emphasized that relying on individual nuclear features in NIFTP cannot differentiate it from benign reactive changes due to their overlapping features, and it is not reliable to even distinguish NIFTP from other PTCs.…”
Section: Discussionmentioning
confidence: 99%
“…NIFTP typically shows subtle PTC‐like nuclear features which could overlap anywhere on the spectrum of classical PTC and reactive nuclear atypia, though it is generally thought that these tumors need to be managed conservatively with lobectomy instead of total thyroidectomy due to their uncertain malignant potential but likely indolent behavior 15,19,22,23 . While a nuclear scoring scheme could introduce a more structured approach to classification, concerns about intra‐ and inter‐observer variability and inconsistent reports remain 14,24,25 . Zajkowska and Strickland addressed the problem with the NIFTP entity 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Renshaw and Gould explained their motivation to over-diagnose uncertain cases rather than under-diagnose them in North American practice [51]. The gap between North America and the rest of the world became wider, and non-invasive encapsulated follicular variant PTC accounted for nearly 30% of PTC in North American practice [22,39,40,52,53], whereas it was low (1-5%) in most Asian thyroid practices [24,25,[41][42][43][44]48], some European institutes [14,[54][55][56], and a few US centers [25,57]. Hodak et al discussed this overdiagnosis in their excellent commentary, suggesting that for many patients with thyroid cancer, we may often be violating the important dictum primum non nocere (first, do no harm patients) [58].…”
Section: Ras-like Ptcmentioning
confidence: 99%